2007
DOI: 10.1016/j.ymgme.2007.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic derangement of methionine and folate metabolism in mice deficient in methionine synthase reductase

Abstract: Hyperhomocyst(e)inemia is a metabolic derangement that is linked to the distribution of folate pools, which provide one-carbon units for biosynthesis of purines and thymidylate and for remethylation of homocysteine to form methionine. In humans, methionine synthase deficiency results in the accumulation of methyltetrahydrofolate at the expense of folate derivatives required for purine and thymidylate biosynthesis. Complete ablation of methionine synthase activity in mice results in embryonic lethality. Other m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
122
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 99 publications
(131 citation statements)
references
References 56 publications
8
122
0
1
Order By: Relevance
“…In our previous study, we reported that adult Mtrr gt/gt males (but not females) weighed significantly less than their wild-type littermates [24]. In this study there were no differences between Mtrr gt/gt males and Mtrr gt/gt females in delay rate, embryonic length, embryonic weight, placental weight or VSD incidence (data not shown).…”
Section: Effects Of Gendersupporting
confidence: 37%
See 4 more Smart Citations
“…In our previous study, we reported that adult Mtrr gt/gt males (but not females) weighed significantly less than their wild-type littermates [24]. In this study there were no differences between Mtrr gt/gt males and Mtrr gt/gt females in delay rate, embryonic length, embryonic weight, placental weight or VSD incidence (data not shown).…”
Section: Effects Of Gendersupporting
confidence: 37%
“…It is possible that placental defects contributed to the increased resorptions, as well as to the developmental delay and growth retardation that we observed in the embryos. In mice, Mtrr is highly expressed in the labyrinth layer of the placenta at E9.5 [24]. Appropriate expression of differentially methylated imprinted genes is necessary for proper placental and fetal growth [26], and Mtrr genotype, by altering AdoMet/AdoHcy ratios, may influence the methylation capacity in the placenta.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations